The global burden of neck pain: estimates from the Global Burden of Disease 2010 study. Issue 7 (30th January 2014) - Hoy, Damian; March, Lyn; Woolf, Anthony; Blyth, Fiona; Brooks, Peter; Smith, Emma; Vos, Theo; Barendregt, Jan; Blore, Jed; Murray, Chris; Burstein, Roy; Buchbinder, Rachelle
Abstract : Objective: To estimate the global burden of neck pain. Methods: Neck pain was defined as pain in the neck with or without pain referred into one or both upper limbs that lasts for at least 1 day. Systematic reviews were performed of the prevalence, incidence, remission, duration and mortality risk of neck pain. Four levels of severity were identified for neck pain with and without arm pain, each with their own disability weights. A Bayesian meta-regression method was used to pool prevalence and derive missing age/sex/region/year values. The disability weights were applied to prevalence values to derive the overall disability of neck pain expressed as years lived with disability (YLDs). YLDs have the same value as disability-adjusted life years as there is no evidence of mortality associated with neck pain. Results: The global point prevalence of neck pain was 4.9% (95% CI 4.6 to 5.3). Disability-adjusted life years increased from 23.9 million (95% CI 16.5 to 33.1) in 1990 to 33.6 million (95% CI 23.5 to 46.5) in 2010. Out of all 291 conditions studied in the Global Burden of Disease 2010 Study, neck pain ranked 4th highest in terms of disability as measured by YLDs, and 21st in terms of overall burden. Conclusions: Neck pain is a common condition that causes substantial disability. With aging global populations, further research is urgently needed to better understand the predictors and clinical course of neck pain, as well as the ways in which neck pain can be prevented and better managed.